An Interpretation of the Light Design of Roger Deakins’ Works from the Perspective of Film Semiotics - Tongyao, Jia; Weizhang, Jia (Amazonia Investiga, 2022)
Semiotics offers an effective way for the study of light design, and has important value for the theoretical study of lighting in films. The light symbol is of conventionality, iconicity and indication. The American Cinematographer, Roger Deakins, has won two Academy Awards for Best Cinematography and been nominated 15 times for his works, which shows his high attainments in light design. In his creation, he used a variety of light design, so that the film can better show the plot of the script, restore the characters and scene modeling, which, at bottom, is a flexible use of the light symbol. With case study, literature study and interdisciplinary research, this paper takes Roger Deakins’ works as an example, attempting to interpret the light design with the theory of film semiotics from various angles, and seeking for new discoveries for the theoretical research and practical creation in light design.